Pendampingan dan Sosialisasi Penerapan Kekayaan Intelektual bagi UMKM di Kabupaten Bintan - Yudy Sunantri; Henricus Yayan Setyanto; Hary Jocom (Universitas Kristen Satya Wacana Salatiga, 2023)
The Micro, Small and Medium Enterprises (MSME) business activities are an integral part in society life. Because business activities are related to other human activities. Due to business activities, part of industry starts creating products. Every business actor will compete in creating, and marketing their products. Business products demands Intellectual Property Rights in order to be protected from unfair competition. Intellectual Property Rights takes a part and serves the business world, including the Micro, Small and Medium Enterprises (MSME) group. There is unvarying understanding that Intellectual Property needed as protector making many MSME are not registered yet. In addition to cost constraints and access difficulties are also considered as other causes of MSME actors not getting information about the registration of Intellectual Property Rights; The objectives of the activity include (1) MSME actors in Bintan district get information about the registration of Intellectual Property Rights (2) Providing additional information for the wider community in general and MSME actors in particular knowledge and awareness of the importance of registering Intellectual Property, so that if it is registered legally, it will directly receive legal protection (3) building the community group competence; (4) increasing public awareness of potential tourism which will have an impact on improving the economic aspects.